Reduction of catastrophic health care expenditures by a community-based health insurance scheme in Gujarat, India: current experiences and challenges. - Ranson, Michael Kent (World Health Organization, 2002)
OBJECTIVE: To assess the Self Employed Women's Association's Medical Insurance Fund in Gujarat in terms of insurance coverage according to income groups, protection of claimants from costs of hospitalization, time between discharge and reimbursement, and frequency of use. METHODS: One thousand nine hundred and thirty claims submitted over six years were analysed. FINDINGS: Two hundred and fifteen (11%) of 1927 claims were rejected. The mean household income of claimants was significantly lower than that of the general population. The percentage of households below the poverty line was similar for claimants and the general population. One thousand seven hundred and twelve (1712) claims were reimbursed: 805 (47%) fully and 907 (53%) at a mean reimbursement rate of 55.6%. Reimbursement more than halved the percentage of catastrophic hospitalizations (>10% of annual household income) and hospitalizations resulting in impoverishment. The average time between discharge and reimbursement was four months. The frequency of submission of claims was low (18.0/1000 members per year: 22-37% of the estimated frequency of hospitalization). CONCLUSIONS: The findings have implications for community-based health insurance schemes in India and elsewhere. Such schemes can protect poor households against the uncertain risk of medical expenses. They can be implemented in areas where institutional capacity is too weak to organize nationwide risk-pooling. Such schemes can cover poor people, including people and households below the poverty line. A trade off exists between maintaining the scheme's financial viability and protecting members against catastrophic expenditures. To facilitate reimbursement, administration, particularly processing of claims, should happen near claimants. Fine-tuning the design of a scheme is an ongoing process - a system of monitoring and evaluation is vital.